2008
DOI: 10.2341/07-124
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Er,Cr:YSGG Laser Treatment on Microtensile Bond Strength of Adhesives to Enamel

Abstract: The current trend towards minimum-intervention dentistry has introduced laser technology as an alternative technique for cavity preparation. This study assessed the null hypothesis that enamel prepared either by Er,Cr:YSGG laser or conventional diamond bur is equally receptive to adhesive procedures. The buccal and lingual surfaces of 35 sound human molars were prepared with Er,Cr:YSGG laser or a medium-grit diamond bur. One etch&rinse (OptiBond FL) and three self-etch adhesives (Adper Prompt L-Pop, Clearfil S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
86
1
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 18 publications
9
86
1
9
Order By: Relevance
“…In addition, microcracks were observed in most laser irradiated samples, indicating surface damage caused by laser irradiation. 9 Cardoso and others 22 reported that morphological alterations produced by Er,Cr:YSGG laser-irradiation adversely influenced the bonding effectiveness of adhesives to dentin. Some studies present the acid resistance of dentin by laser, reporting the possibility of erbium lasers to diminish the solubility of irradiated dentin when immersed in an acid solution.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, microcracks were observed in most laser irradiated samples, indicating surface damage caused by laser irradiation. 9 Cardoso and others 22 reported that morphological alterations produced by Er,Cr:YSGG laser-irradiation adversely influenced the bonding effectiveness of adhesives to dentin. Some studies present the acid resistance of dentin by laser, reporting the possibility of erbium lasers to diminish the solubility of irradiated dentin when immersed in an acid solution.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to better infiltration and proper coverage of demineralized dentin. 9 Cardoso et al 26 reported that the bonding efficacy of adhesives to laser-irradiated dental tissue depends not only on the structural substrate alterations induced by the laser but also on the characteristics of the adhesive employed. Adper Easy One contains nanofiller particles in its composition.…”
Section: Discussionmentioning
confidence: 99%
“…Different adhesive systems can interact differently with lased surfaces. 26 Adper Easy One, a one-bottle self-etching adhesive formulation, includes a carefully balanced combination of phosphoric acid esters, water, and methacrylates in order to optimize stability. In addition, it contains bonded nanosilica fillers.…”
Section: Discussionmentioning
confidence: 99%
“…16) Cardoso et al 23) suggested that the irregularities on the laserirradiated dentin were so prominent that they may reduce the bond strength by preventing uniform stress distribution at the adhesive-dentin interface. Moreover, because of these irregularities, the thickness of the adhesive layer was not uniform on the dentin surface, thus resulting in diminished bonding effectiveness.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…Thus the denatured collagen fibrils are fused together and poorly attached to the underlying unaffected dentin, preventing proper dentin hybridization. 23) These altered microstructures would hamper the infiltration of primer and the hybrid layer would become more susceptible to hydrolysis. 24) Also, it has been demonstrated that the denatured organic matrix blocks the diffusion pathways of adhesive in dentin.…”
Section: ⅳ Discussionmentioning
confidence: 99%